1997
DOI: 10.1037/0096-1523.23.4.1232
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving and tracking kinesthetic stimuli: Further evidence of motor–perceptual interactions.

Abstract: Two experiments pursued previous studies (P. Viviani & P. Mounoud, 1990; P. Viviani & N. Stucchi, 1989) on motor-perceptual interactions. The right arm of blindfolded participants was moved passively along elliptic trajectories. Kinematics was either coherent or at variance with the relation (two-thirds power law) observed in active movements. In Experiment 1 participants compared the horizontal and vertical extent of the ellipses. Kinematics affected aspect ratio discrimination: The direction along which the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
1
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 74 publications
7
54
1
8
Order By: Relevance
“…Additionally, visual and kinesthetic stimuli provide appropriate guidance in motion-tracking tasks only if they comply with this law (28). Moreover, a kinesthetic-based distortion in the perceived geometrical form of the movement's path was obtained when the hand of a blindfolded subject was passively moved in a way violating the 2/3 power law (29). All these observations are consistent with the activations seen in the postcentral gyrus in response to this law.…”
Section: Discussionsupporting
confidence: 78%
“…Additionally, visual and kinesthetic stimuli provide appropriate guidance in motion-tracking tasks only if they comply with this law (28). Moreover, a kinesthetic-based distortion in the perceived geometrical form of the movement's path was obtained when the hand of a blindfolded subject was passively moved in a way violating the 2/3 power law (29). All these observations are consistent with the activations seen in the postcentral gyrus in response to this law.…”
Section: Discussionsupporting
confidence: 78%
“…Studies of kinesthetic perception have shown the existence of biases in the estimation of distances in tactile-kinesthetic tasks such as blindfolded triangle completion (Klatzky, 1999). The geometry of perceived haptic space can be distorted by temporal factors (Dupin, Hayward, & Wexler, 2015;Lederman, Klatzky, Collins, & Wardell, 1987;Yusoh, Nomura, Sakamoto, & Iwabu, 2012), movement speed (Kazunori, Akinori, Daisuke, & Ito, 2006;Viviani, Baud-Bovy, & Redolfi, 1997;Wapner, Weinberg, Glick, & Rand, 1967;Whitsel et al, 1986), memory (Chieffi, Conson, & Carlomagno, 2004;Gentaz & Hatwell, 1999;Millar & Al-Attar, 2004) and the configuration of the body, notably the hands (Kaas & Mier, 2006) or the head and body (Luyat, Gentaz, Corte, & Guerraz, 2001). Biases in the perception of orientation have been observed when participants have to orient a bar in order to make it parallel in threedimensional space to another bar (Kappers, 1999;Kappers & Koenderink, 1999).…”
mentioning
confidence: 99%
“…Visual experiments revealed that a dot moving along a curved shape was perceived as the most constant when the relation between its velocity and the curvature of the traveled trajectory followed the 1/3-power law, even when the velocity variations exceeded 200% [43]. The relevance of this law has also been studied in the kinesthetic modality and revealed the same perceptual constraint [45]. This law can partly explain why the ellipse and the loops from the previous experiment were confounded.…”
Section: The 1/3-power Lawmentioning
confidence: 65%
“…As mentioned in the introduction, the velocity profile is a very important characteristic of a gesture, which may be involved at different levels of perception of a biological movement both in the visual system [41,43] and in the kinesthetic one [45]. Here we aim at investigating if this parameter is also a relevant cue to identify a drawn shape from a friction sound.…”
Section: A Synthesis Model Of Friction Soundsmentioning
confidence: 99%